The attitude towards online shopping among student of Universiti Teknologi MARA Kampus Bandaraya Melaka / Siti Aishah Ishar - Ishar, Siti Aishah (Faculty of Business and Management, 2018)
The present research was conducted at UiTM Bandaraya Melaka. This research and study was conducted to know the attitudes towards Online Shopping among student of UiTM Bandaraya Melaka. It is also indicate the relationship between the dependent variable (attitudes towards online shopping) and independent variable (perceived ease of use, perceived benefits, prior online purchased experienced and perceived website quality). This research is quantitative research and the data used for the study was collected using distribution of questionaires. There were 266 students of UiTM Bandaraya Melaka took part in answering the questionnaires. The data obtained from the questionaires were analysed by using SPSS software. As a summary, after analysing the data collected, the result showed that only two has significant relationship with the dependent variable, which are prior online purchased experienced and perceived website quality.